Texture Classification Using Texture-based Feature Extraction Algorithms - Saeed, Shvan Abdullah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Texture is one of the significant characteristics used in identifying objects of interest or regions in an image. Texture is an important characteristic of surface property in visual scenes and is a power cue in visual perception. The real applications of texture classification are remote sensing, medical imaging, industrial inspection and pattern recognition. Texture images are highly affected by rotation and illumination. Extracting texture features that are rotation-invariant and insensitive to illumination with high classification accuracy is still a challenge. Texture analysis has been a popular area of study in computer vision for decades. In this thesis, six texture-based feature extractors that may perform variously to rotation and illumination are used namely Local Binary Patterns (LBP), Complete Local Binary Patterns (CLBP), Segmentation-based Fractal Texture Analysis (SFTA), Histogram of Oriented Gradients (HOG), Rotation Invariant Histogram of Oriented Gradients (RIHOG) and Haralick feature extractor. They are implemented and tested on three benchmark texture databases, such as The Columbia-Utrecht Database (CUReT), University of Oulu Texture database (OUTex) and Textured Surfaces Database. For feature matching, two classifiers are used namely Naive Bayes and Support Vector Machines (SVM). A comparative study is presented at the end of the experimental evaluations on texture classification.

ÖZ: Doku, bir görüntüdeki ilgi alanı veya nesneyi tanımlamak için kullanılan belirgin bir özelliktir. Görsel görünüm için kullanılan yüzey özelliklerinin önemli bir belirleyicisi dokudur ve görsel algıda kullanılan güçlü bir ipucudur. Doku sınıflandırmanın gerçek hayattakiuygulamaları uzaktan algılama, tıbbi görüntüleme, endüstriyel denetim ve örüntü tanımadır. Doku görüntüleri, döndürme ve ışıklandırmadan dolayı fazlaca etkilenirler. Döndürmeye duyarsız ve ışıklandırmadan etkilenmeyen doku özniteliklerinin yüksek bir sınıflandırma yüzdesiyle çıkartılması zor bir işlemdir. Doku analizi, bilgisayarla görü alanında çalışılan popüler bir alandır. Bu tezde, döndürmeye ve ışıklandırmaya karşı farklı tepkiler veren altıtanedokuya dayalı öznitelik çıkarma yöntemi kullanılmıştır. Bu yöntemler, Yerel İkili Örüntüler (LBP), Tamamlanmış Yerel İkili Örüntüler (CLBP), Bölütlemeye Dayalı Fraktal Doku Analizi (SFTA), Gradient’lere Yönelik Histogramlar (HOG), Döndürmeye Duyarsız Gradient’lere Yönelik Histogramlar (RIHOG) ve Haralick Öznitelik Çıkartıcı yöntemidir. Bu yöntemler üç farklıdoku veritabanı üzerinde uygulanmış ve test edilmiştir. Kullanılan veritabanları Columbia Utrecht Veritabanı (CUReT), Oulu Üniversitesi Doku Veritabanı (OUTex) ve Dokusal Yüzeyler Veritabanı’dır. Öznitelik eşleştirme işlemi için Naïve Bayes ve Destek Vektör Makinesi (SVM) sınıflandırıcıları kullanılmıştır.Deneylerin sonunda, doku sınıflandırma değerlendirilmiş ve karşılaştırmalı bir çalışma sunulmuştur.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2018. Supervisor: Assoc. Prof. Dr. Önsen Toygar.
Keywords: Computer Engineering; Texture Classification; Texture classification, feature extraction, texture-based methods